Usability and acceptability of a hypothermia monitoring device in a community setting - Mukane, Madhuri; Gage, Annika; Choubey, Priyanka (International Journal Of Community Medicine And Public Health, 2020)
Background: The present pilot study aimed to test the usability and acceptability of the hypothermia monitoring device, i.e., temp watch, among the mothers/caregivers of low birth infants (LBW) and community health workers (ASHA workers) who visited them. Methods: Eligible LBW new-borns (<2500 grams) were recruited after written informed consent from parents and were followed-up for 28 days with intermittent visits from assigned ASHA workers. The parents recorded hypothermia episodes and KMC hours in a patient diary. Feedback was taken from these mothers and ASHA workers at the end of study. Results: The weight gain at 28th day of the recruited babies was significant (p=0.01) as compared to the weight at enrolment on day 0. Among the recruited population (n=50 LBW infants), 57% of the subjects reported the device alerted for hypothermia at least once a week. All the mothers of the recruited babies thought that the temp watch device was useful for hypothermia monitoring and the alerts helped in maintaining the baby’s temperature. All ASHA workers were satisfied with the device and reported a positive behavioral change in the mothers KMC hours at the end of the study. Conclusions: The temp watch was useful in hypothermia monitoring in LBW infants in a low resource home setting. The usability and acceptability of the device was tested in mothers and ASHA workers with positive feedbacks from both populations. This suggests a need for the intro-duction of the device as a community-based intervention for hypothermia monitoring in LBW infants.